Critical Making Takes a Holiday - Pinto, Laura; Blue, Levon (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2021)
“Making” is used to engage young people into ways of collaborative learning using materials, resources, and equipment in makerspace environments. In this paper we attempt to interrogate the popular maker movement’s “state-of-the-actual” in education with respect to its criticality. We begin by conceptually clarifying the movement with respect to its semantic disarray. Next, we situate maker and production pedagogies philosophically, and discuss how their thrust and emphasis create both hidden and overt curricula that can either cultivate or silence criticality. Finally, we problematize the effects of uncritical exuberance for educational making, and propose concrete strategies in which educators can nudge their own makerspaces into more state-of-the-art environments that promote criticality.